A közérdekű munka speciális jellegének főbb vonásai - Mónusné Kiss, Katalin (Debreceni Jogi Műhely, 2006)
In Hungary there are two types of punishments: principal punishments and supplementary punishments. I examined the labour in the public interest, which is one of the principal punishments. Judges use this punishment barely than imprisonment, fine. Difficult to use this punishment, because it needs many preliminary works. I examined the labour in the public interest’s ruling from the 1950.:II. Criminal Code of General Part to nowadays.In Hungary a person sentenced to labor in the public interest is obligated to perform the work defined for him in the court sentence. Only such work may be ordered as work in the public interest which the convict, in light of his health condition and education, is presumed to be capable of performing. There are many problems in rule of the labour in the public interest, for example one day of work in the public. As rule of the Criminal Code punishment shall be six hours of work, but other rule is, punishment shall be 4-8 hours of work for one day.Other interesting rule is, the imprisonment substituting labour in the public interest or the remaining part thereof shall be established in such a way that one day of labour in the public interest shall correspond to one day of imprisonment. In my opinion it would be better, if the imprisonment substituting labour in the public interest or the remaining part thereof shall be established in fine.On the other hand I suggested to use this punishment if a person younger than 18 years old. I think if a person is 16 years old, this punishment can be more effective than other punishments.I found many differences, and many similarities between Hungarian and international Criminal Codes, Propositions, and finally I wrote some important, new point to change the rules.